PENGARUH KOMUNIKASI PEMASARAN TERHADAP LOYALITAS NASABAH (STUDI KASUS BANK XYZ SYARIAH CABANG BOGOR) - Rahmatullah Rahmatullah (Institute for Research and Community Empowerment (LPPM TAZKIA), 2009)
The existence of printings and electronics media stimulates business owner, not only in the offering of the products and service quality, but also solid positioning implementations through quality standard and service quality. These particular effort intends to overwhelm the mind of customer through products and services offered. Communications Marketing Strategy Planning becomes irresistibly required to prevent loss from mistaken implementations of Marketing Communications. In accordance to the Marketing Communications Programs taken gradually by XYZ Syariah Bank, Writer intends to understand the Customer Loyalty of XYZ Syariah, also to discover further connections between Marketing Communication and Customer Loyalty, and identifying the customer expectations and the performance of marketing communications programs Research Method are descriptive correlations, data gathering by questionnaires, data processed by SPSS 13,0. Minitab 14 for IP Matrix presentation, linear numeric scale of semantic differential, Spearman Correlations Analysis, research population is the customers of XYZ Syariah Bank, therefore the sample are 60 persons using judgment sampling techniques in sample drawings. Result indicates 78% of customers are loyal, few programs positively related tocustomers loyalty, which is image buildings, sponsorships, attractively cheap margin and high profit sharing. For customer opinion on proper performance and importance programs are image buildings, cheap margin for financing, and high profit share in funding. On sought to results, XYZ Syariah Bank may emphasize on programs related in positive fashion with customer loyalty, yet improves other marketing communications programs. Customer loyalty also need to be look after, as same as performance of marketing communications programs, in order to fit customers perceptions of importance.